An optimized ultrasound detector for photoacoustic breast tomography. Issue 3 (28th February 2013) - Xia, Wenfeng; Piras, Daniele; van Hespen, Johan C. G.; van Veldhoven, Spiridon; Prins, Christian; van Leeuwen, Ton G.; Steenbergen, Wiendelt; Manohar, Srirang
Abstract : Purpose: : Photoacoustic imaging has proven to be able to detect vascularization‐driven optical absorption contrast associated with tumors. In order to detect breast tumors located a few centimeter deep in tissue, a sensitive ultrasound detector is of crucial importance for photoacoustic mammography. Further, because the expected photoacoustic frequency bandwidth (a few MHz to tens of kHz) is inversely proportional to the dimensions of light absorbing structures (0.5–10+ mm), proper choices of materials and their geometries and proper considerations in design have to be made to implement optimal photoacoustic detectors. In this study, we design and evaluate a specialized ultrasound detector for photoacoustic mammography. Methods: : Based on the required detector sensitivity and its frequency response, a selection of active material and matching layers and their geometries is made leading to functional detector models. By iteration between simulation of detector performances, fabrication and experimental characterization of functional models an optimized implementation is made and evaluated. For computer simulation, we use 1D Krimholtz–Leedom–Matthaei and 3D finite‐element based models. Results: : The experimental results of the designed first and second functional detectors matched with the simulations. In subsequent bare piezoelectric samples the effect of lateral resonances was addressed and their influence minimized by subdicing the samples. Consequently, using simulations, a final optimized detector was designed, with a center frequency of 1 MHz and a −6 dB bandwidth of 0.4–1.25 MHz (fractional bandwidth of ∼80%). The minimum detectable pressure was measured to be 0.5 Pa. Conclusions: : A single‐element, large‐aperture, sensitive, and broadband detector is designed and developed for photoacoustic tomography of the breast. The detector should be capable of detecting vascularized tumors with 1–2 mm resolution. The minimum detectable pressure is 0.5 Pa, which will facilitate deeper imaging compared to the current systems. Further improvements by proper electrical grounding and shielding and implementation of this design into an arrayed detector will pave the way for clinical applications of photoacoustic mammography.